Sex and Race Disparities in Mortality and Years of Potential Life Lost Among People With HIV: A 21-Year Observational Cohort Study. (19th December 2022) - Pellegrino, Rachael A; Rebeiro, Peter F; Turner, Megan; Davidson, Amber; Best, Noelle; Shaffernocker, Chandler; Kheshti, Asghar; Kelly, Sean; Raffanti, Stephen; Sterling, Timothy R; Castilho, Jessica L
Abstract: Background: Since the availability of antiretroviral therapy, mortality rates among people with HIV (PWH) have decreased; however, this does not quantify premature deaths among PWH, and disparities persist. Methods: We examined all-cause and premature mortality among PWH receiving care at the Vanderbilt Comprehensive Care Clinic from January 1998 to December 2018. Mortality rates were compared by demographic and clinical factors, and adjusted incidence rate ratios (aIRRs) were calculated using multivariable Poisson regression. For individuals who died, age-adjusted years of potential life lost (aYPLL) per total person-years living with HIV were calculated from US sex-specific life tables, and sex and race differences were examined using multivariable linear regression. Results: Among 6531 individuals (51% non-Hispanic [NH] White race, 40% NH Black race, 21% cis-gender women, 78% cis-gender men) included, 956 (14.6%) died. In adjusted analysis, PWH alive in the most recent calendar era (2014–2018) had decreased risk of mortality compared with those in the earliest calendar era (1998–2003; aIRR, 0.22; 95% CI, 0.17–0.29), and women had increased risk of death compared with men (aIRR, 1.31; 95% CI, 1.12–1.54). Of those who died, Black women had the highest aYPLL (aIRR, 592.5; 95% CI, 588.4–596.6), followed by Black men (aIRR, 470.7; 95% CI, 468.4–472.9), White women (aIRR, 411.5; 95% CI, 405.6–417.4), then White men (aIRR, 308.6; 95% CI, 308.0–309.2). In adjusted models, higher YPLL remained associated with NH Black race and cis-gender women, regardless of HIV risk factor. Conclusions: Despite marked improvement over time, sex disparities in mortality as well as sex and race disparities in YPLL remained among PWH in this cohort. Abstract : Despite marked improvement in HIV mortality over the last 21 years, women continued to have higher mortality rates than men. Additionally, women and Black individuals had higher premature mortality, by years of potential life lost, over this time period.